Sistema de compartilhamento de arquivos desenvolvido em linguagem Java - Pereira, Marcelo Veiga (2019)
The Java programming language has classes that enable the communication of computers in a network, using sockets. Auxiliary classes for reading and writing in data stream allow communication in text and binary format. This work explores the use of sockets through the development of a series of client and server programs with different forms of communication until the transfer and sharing of binary files using sockets protected by cryptography.